Kajian Peraturan Perjanjian Lisensi Ciptaan Lagu dan Peranan LMK Dalam Undang-Undang Hak Cipta di Indonesia - Vincentius Adhi Pramana; Retno Dewi Pulung Sari (JURNAL HUKUM PELITA, 2025)
The phenomenon of copyright often becomes problematic for both songwriters and users. This occurs because the rights of songwriters are used arbitrarily without their permission. The government, through the LMKN (National Institute for Musical Research and Community Empowerment) and LMK (National Institute for Musical Research and Community Empowerment), which have played roles according to their respective competencies, needs to reorganize and accommodate the parties involved, namely songwriters and users. Law No. 28 of 2014 concerning Copyright has regulated how the regulation and licensing process for the use of songs owned by a songwriter. This research is a normative juridical study using primary legal materials, namely Law No. 28 of 2014 concerning Copyright and Government Regulation No. 56 of 2021 concerning Management of Song and Music Copyright Royalties. In addition, the author also used secondary legal materials, namely books and several journals related to this research. The results of this study indicate that the role of LMKN and LMK has not fulfilled and accommodated the rights of songwriters and users. This problem becomes even more pronounced when song users lack legal permission from the songwriters. Therefore, changes or revisions to the regulations governing song creation and use are needed to ensure fairness for both parties